Laboratory and field performance of manual seed drill for sowing jute and tiny seeds - SHAMBHU, V B; THAKUR, A K (The Indian Journal of Agricultural Sciences, 2019)
Jute (Corchorus olitorius) is one of the bast fibre producing cash crops in the world and it is the second most important textile fibre next to cotton. Jute plays a significant role in livelihood of the resource poor small and marginal farmers in India. Jute farmers generally follow broadcast method of jute sowing where the placement of seeds at proper soil depth and uniformity cannot be attained. It becomes extremely difficult to place correct quantity of tiny seeds manually at desired depth of soil for optimum plant population due to small size of seeds. On the other hand,line sowing of small seeds like jute, mustard, sesame etc. is very much desirable to save seed as well as maintaining plant population, reduce cost of sowing, weeding and thinning. Therefore, a simple manually drawn multi-row seed drill for jute as well as small seeds of other crops was developed and evaluated in laboratory and field conditions. It ensures uniform germination and proper crop stand on one hand and facilitates other post sowing operations like weeding and thinning, fertilizer application, plant protection measure, irrigation and harvesting of jute crop on the other hand. The developed seed drill required only 75.16 N of draft for its operation which is within the capacity of an average man. It was found that the time required in line sowing for jute is only 6 man-hours/ha which is same as compared to traditional method of sowing.